METHODS OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE: INNOVATIONS AND TRADITIONS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article examines modern methods of teaching Russian as a foreign language, combining traditional and innovative approaches. It analyzes classical methods of teaching Russian as a foreign language, such as grammar-translation and audio-lingual methods, as well as modern communicative, project-based, and digital technologies. Particular attention is paid to the role of an intercultural approach and the use of information and communication technologies in the educational process. The article also substantiates the need to integrate traditional and innovative methods to improve the effectiveness of teaching Russian as a foreign language and develop students' communicative competence